STICS soil-crop model Conceptual framework, equations and uses - Beaudoin, Nicolas; Lecharpentier, Patrice; Ripoche-Wachter, Dominique; Strullu, Loïc; Mary, Bruno; Léonard, Joël; Launay, Marie; Justes, Eric (éditions Quae, 2023)
The STICS crop model has been developed since 1996 at INRA (French National Institute for Agronomic Research) in collaboration with other research and technical institutes. The model syntheses, illustrates and concretizes an important part of the French agronomic knowledge as a point of view on the field and cropping systems working. The formalisations of the STICS crop model presented in this book can be considered as references used in the framework of crop sciences. They will help professionals and students in the partitioning and understanding of the complex agronomic system. The book arrangement relies on the way the model designs the crop-soil system functioning, each chapter being devoted to a set of important functions such as growth initiation, yield onset, water uptake, transformation of organic matter etc. One chapter deals with the cropping system and long term simulations and the final chapter is about the involvement of the user in terms of option choices and parameterization. If this book is mainly intended for scientists who use the STICS model, it can also be useful for agronomists, crop modellers, students and technicians looking for elementary formalizations of the crop-soil system functioning.